2021
DOI: 10.1021/acsabm.0c01335
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Photocatalytic Antibacterial

Abstract: Pathogens on wounds and infected tissues or pathogens in drinking water or public facilities have been doing great harm in human life. Because of booming drug resistance and superbacteria, the abuse or excessive use of antibiotics during systemic treatment has caused a global antibiotic crisis. However, it usually takes a long time to develop antibiotics. In recent years, photocatalytic antibacterial agents have no drug resistance and side-effects due to their rapid and efficient bactericidal efficacy. They ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 186 publications
0
66
0
Order By: Relevance
“…52−54 Furthermore, several studies have shown the antibacterial effectiveness of synthesized NPs to be lower than 100%. 13 For example, Fe-doped ZnO, Nb/N-doped ZnO, and Cu-doped TiO 2 have been reported to have antibacterial efficiencies of approximately 90%. 55−57 Other results have highlighted the value of having distinct performances for the activated and nonactivated treatments.…”
Section: ■ Introductionmentioning
confidence: 99%
“…52−54 Furthermore, several studies have shown the antibacterial effectiveness of synthesized NPs to be lower than 100%. 13 For example, Fe-doped ZnO, Nb/N-doped ZnO, and Cu-doped TiO 2 have been reported to have antibacterial efficiencies of approximately 90%. 55−57 Other results have highlighted the value of having distinct performances for the activated and nonactivated treatments.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition to ZnO and g‐C 3 N 4 , other photocatalysts, such as molybdenum trioxide (MoO 3 ), tungsten trioxide (WO 3 ), and bismuth trioxide (Bi 2 O 3 ) have also been synthesized and exploited in antimicrobial nPCT. [ 58 ]…”
Section: Optical Stimulation‐based Npasmentioning
confidence: 99%
“…Nanosized doped semiconductor oxides (SO) have shown improved biocidal and photocatalytic properties. They have been applied as antifungal agents, 1 antibacterial agents, 2 antivirals in agriculture, 3 and photocatalysts for wastewater treatment. 4 To improve these properties, SO are typically doped with transition metals (Mn, Fe, Cr, Cu), 5 rare earth elements (Ce and Er), 6 and noble metals (Au, Ag, Pt 7 ).…”
Section: Introductionmentioning
confidence: 99%